Criterios para la adopción y revocatoria de medidas de protección en delitos de violencia intrafamiliar y su implicación en la presunción de inocencia. - Gavilán Pasto, Galuth Estefanía (2022)
With the purpose of protecting those who are at risk of violence against women or members of the family, protection measures are ratified in favor of those who are considered victims of violence, for which the present research work seeks to know the adoption of protection measures in favor of the victims in cases of domestic violence, However, beyond the sanctions that can be executed for those who cause violence, there are other important aspects to consider, such as the inadequate use of protection measures by those who have in favor of such measures, who seek to satisfy their interests and whims, thus losing the meaning of the law and its protection. The object of the study is to determine the protection measures adopted in cases of domestic violence and their correct revocation after the state of innocence of the accused is ratified, in order to avoid affecting the rights of the innocent person, specifically personal freedom, since by imposing measures against him/her, his/her freedom of movement is limited, which upon obtaining an acquittal for not proving his/her responsibility, the judge must revoke all the protection measures imposed against him/her. The research is applied, and used the levels of Descriptive - Explanatory research with Deductive, Analytical, Synthetic methods following the line of research in the legal area, supported by a descriptive, documentary - bibliographic research, in addition to quantitative and qualitative approach.